The roles of vitamin B12, 25(OH)D, and folate in primary nocturnal enuresis: A single center experience - Keles, Ahmet; Karakeci, Ahmet; Onur, Rahmi (Bayrakol Medical Publisher, 2024)
Aim: In this study, we investigated the connections between children born late preterm (LPT) and their susceptibility to nocturnal enuresis, examining their vitamin B12, folate, iron, and 25(OH)D levels. Material and Methods: From April 2018 to December 2020, the research group comprised 146 children with PNE who appeared at state hospital urology clinics, whereas the control group included 102 healthy children who presented at the pediatric clinics. Primary nocturnal enuresis was characterized as having more than four wet nights per week in children aged 5 to 13 years. Both groups' hospital records were compared in terms of age, height, weight, vitamin B12, folate, ferritin, and iron levels. Results: There was no difference found in demographic characteristics between our study and control groups. In agreement with the literature, the mean vitamin B12, 25(OH)D, and folate levels were significantly lower in the enuresis group than in the control group. Discussion: The delayed CNS development or the onset of sleep problems may be caused by low levels of vitamin B12, folate, and 25(OH)D in PNE patients. To find out how PNE and folate levels are related, a more extensive series is required.
Keywords: Vitamin B12; 25(OH)D; Folate; Iron; Primary Nocturnal Enuresis